Impact of the COVID-19 pandemic on utilization of mental health services among children and adolescents using an interrupted time series analysis - Fumihiro Endo; Yuji Hiramatsu; Hiroo Ide (Scientific Reports)
Abstract This study aimed to examine the impact of both the initial state of emergency (SOE) imposed from April to May 2020 in response to the COVID-19 pandemic and the COVID-19 outbreak itself on the utilization of mental health services among children and adolescents in Japan during the recent pandemic. We conducted an interrupted time series analysis of the number of mental health visits and average incurred medical expenses, stratified by sex and age group, using monthly medical claims data on 3,029,048 patients for the period from January 2016 to December 2020. It was demonstrated that the SOE resulted in a reduced number of visits for mental health services. After the second outbreak of COVID-19 in Japan, which occurred after the SOE, the number of initial visits and the average incurred medical expenses for mental health services increased notably among girls and adolescent females. The findings of this study suggest that: (1) the provision of mental health services for potential patients with mental disorders was insufficient during the pandemic, and (2) the mental health of girls and adolescent females deteriorated during the pandemic. Early screening and treatment of potentially vulnerable patients with mental disorders should be enhanced during a pandemic.